Reproducing the ankle kinematics by forwards dynamics to evaluate the effect of ankle-foot orthoses - Ferreira, Philippe (2013)
Biomechanics is the scientific domain which deals with the study of biological systems, such as the human body, using physical concepts and mechanical engineering methodologies. It allows for the development of new medical devices and provides a quantitative analysis of the subject being studied. In the present work, the effect of an ankle-foot orthosis (AFO) was studied on a healthy male subject. For this purpose, a biomechanical MB 2D-model was developed in object-oriented multibody (MB) simulation library MOBILE. The model consists of a pair of legs, each one made up of 4 rigid links (thigh, shank, foot and toes), and an additional body to represent the upper-body, totalizing 9 rigid bodies constrained by 9 frictionless hinged joints. Three additional degrees of freedom (DOFs) were attached to the hip so the model can move freely in the plane. Thus, the model has a total of 12 DOFs. Kinematic data acquired in a gait laboratory, with and without AFOs, and was used as time functions to drive the joints. Moreover, a foot contact model was designed based on three Hunt-Crossley’s sphere-plane contacts. The measured ankle kinematics was successfully reproduced using forward dynamics (FD) principles for the stance phase period. In a first approach, barefoot kinematics was reproduced to define the foot properties by adjusting manually the foot parameters and fitting the ankle angle. The ankle moment obtained in the gait lab was used to power the ankle joint. Then, the AFO was added as a linear torsional spring element acting at the ankle joint and the moment powering the ankle joint obtained in the free case was scaled down by a manual optimization until the simulated ankle angle fitted the measured one with orthoses. It was found that the AFO scales down the muscle moment developed at the ankle by 15% when an AFO with equivalent torsional spring stiffness of k=50Nm is used.